2017
DOI: 10.1093/ajh/hpx130
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil Improves L-NG-Nitroarginine Methyl Ester-Induced Preeclampsia With Fetal Growth Restriction-Like Symptoms in Pregnant Mice

Abstract: Tadalafil dilates the placental maternal blood sinuses, which leads to increase PlGF production, and contributes to facilitate fetal growth and improve maternal SBP. Moreover, tadalafil ameliorates glomerular damage by reducing oxidative stress. These results suggest that tadalafil is a candidate for treatment of PE with FGR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 31 publications
2
33
0
1
Order By: Relevance
“…We have recently shown a potential therapeutic effect for tadalafil on PE and FGR in small clinical trials 912 . In addition, our animal experiments have demonstrated that tadalafil treatment elevates maternal urinary excretion of cGMP and dilates the maternal blood sinuses in the placenta, which facilitates fetal growth 13 . These findings led us to hypothesize that tadalafil treatment for PE and FGR may improve neurodevelopment in offspring.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…We have recently shown a potential therapeutic effect for tadalafil on PE and FGR in small clinical trials 912 . In addition, our animal experiments have demonstrated that tadalafil treatment elevates maternal urinary excretion of cGMP and dilates the maternal blood sinuses in the placenta, which facilitates fetal growth 13 . These findings led us to hypothesize that tadalafil treatment for PE and FGR may improve neurodevelopment in offspring.…”
Section: Introductionmentioning
confidence: 78%
“…We used the PE with FGR mouse model induced by L-NAME as described previously, with a small modification 13 . A control group of dams (C dam, n = 5) received 0.5% carboxymethylcellulose (CMC).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 19 20 Our animal experiments demonstrated that tadalafil treatment dilates the maternal blood sinuses in the placenta, which leads to increased placental growth factor (PlGF) production and contributes to the facilitation of fetal growth. 21 In those animal experiments, we can safely presume that tadalafil treatment contributed to the facilitation of fetal growth via mechanisms associated with NO signalling, because the tadalafil treatment was initiated after blood spaces in the placenta were narrowed by the L-NAME treatment and an elevated urinary excretion of cGMP was observed.…”
Section: Introductionmentioning
confidence: 99%